(untitled) (Global Journal of Human-Social Science, 2016)
Oceans Apart discusses the story of a child countering the need of attachment with his parental caregivers. Kiahna and Connor had an illegal affair and the evident birth of a child did not hamper the child to create healthy loving attachment patterns. However it did create the urgency to seek his biological father after his mother’s death. This paper presents the story of Max’s internal working model in close connection to the lovely, intricate-interconnected motherly relationship.